D-Dimer Concentrations and Thromboelastography in Five Dogs With Ischemic Stroke - Koch, Bodil Cathrine; Motta, Luca; Wiinberg, Bo; Westrup, Ulrik; Kristensen, Annemarie Thuri; Skerritt, Geoff; Berendt, Mette; Gredal, Hanne (Frontiers in Veterinary Science, 2019)
Ischemic stroke is a condition increasingly recognized in dogs; however, the number of publications on dogs with ischemic stroke is still limited and hemostatic parameters are infrequently reported. D-dimer levels have been shown to be elevated in people with acute ischemic stroke compared to a healthy control population and it has been proposed that a normal D-dimer can be used to exclude thromboembolism in dogs. In this case series, we report hemostatic parameters, including D-dimer and thromboelastography (TEG) along with clinical and imaging findings for five dogs diagnosed with ischemic stroke. All dogs had a normal D-dimer concentration on presentation. A hypercoagulable state was identified in two dogs based on the results of the TEG, and was suspected in the remaining three cases based on a shortened TEG clot reaction time. Based on the findings in the present cases, a D-dimer within the normal reference range does not seem an appropriate negative predictor for canine ischemic stroke. The demonstration of a possible hypercoagulable state, as identified by the TEG, is an interesting finding which should be explored further to help reveal predisposing hypercoagulable conditions in dogs with ischemic stroke.